The Representation of Corruption in Okky Madasari's Novel "86" and Its Relevance to Moral Values - Khasanah, Indah; Sunanda, Adyana (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to examine the representation of corruption contained in Okky Madasari's novel 86 and see its relevance to moral value education in schools. This research is a descriptive qualitative research whose analysis results are in the form of phenomena. The research data are words, phrases, sentences, dialogs, and paragraphs containing representations of corruption taken from the data source in the form of novel 86. Data analysis uses a semiotic model through heuristic and hermeneutic reading. The results of this study are that in novel 86 by Okky Madasari, there are several forms of corruption representation in the form of bribery as much as 12 data, extortion 6 data, and fraudulent acts 9 data. In addition, there are also internal factors totalling 5 data and external factors totalling 1 data that cause corruption. The results of the study can be used as a teaching of moral values in schools by integrating it into Indonesian language learning in the independent curriculum.